Ustav, populizam i kraj liberalne demokracije - "referendumanija" ugrožava temelje ustavnog poretka - Smerdel, Branko (Array, 2019)
Democracies are at risk to be strangled by the populist demagogues, posturing as the only and true leaders of 'the people', while disregarding constitutional "structure of liberty", meaning that, the parliamentary supremacy, judicial review and, above all, the constitutional limits to the very direct decision making by the voters' constituencies. Referenda are being used ever more, often to push certain decision, which could not pass the parliament. The claim is that there must not be any limits to the power of the people. That phenomenon the most esteemed liberal magazine "The Economist" nicknamed coining the word "referendumania", apparently combining 'a mania' with 'referenda'. It has been received with a lot of sympathy by the general public, in circumstances when the television and the Internet shows all the misery of the numerous assemblies, not only in a new but also in the mature democracies. After the referendum on the Brexit has been used as an instrument of the political struggle in the mother of parliaments, Great Britain, which lead to the ongoing "melting down" of the highly valued British political system, it seems that the worst of prophecies are realized by advancing populist forces in a number of Euroepan states. Republic of Croatia has been for a long time exposed to such treats, by the political groups extremely opposed to governmental policies, first by the Catholic conservatives and most recently by the trade unionists. Due to the very inadequate regulation of the referenda on civil initiatives, whereas the decision is to be made by a majority of those who vote, without any quorum being provided, the posibilites of manipulation are enormous.